THU0662 Impact of the intervention of a multidisciplinary adherence team in clinical outcomes of patients with rheumatoid arthritis and spondyloarthropathies in colombia. (12th June 2018) - Pineda-Tamayo, R.; Sanchez, K.; Alzate, M.-A.; Hernandez-Parra, D.; Echeverry, D.; Ortiz-Salazar, P.; Rojas-Villarraga, A.
Abstract : Background: The multidisciplinary adherence team (MAT) is a interprofessional health care group conformed by a general practitioner, a pharmaceutical chemist and a psychologist, which evaluate the patient to provide a simultaneous multidisciplinary approach focused on promoting strategies to improve adherence to treatment in patients with high disease activity of autoimmune or autoinflammatory pathologies Objectives: To determine the impact of the MAT group intervention on the disease activity and therapeutic adherence of Colombian patients with rheumatoid arthritis (RA) and seronegative spondyloarthropathies (SpA). Methods: A quasi-experimental analytical study was performed where 4.921 RA and 756 SpA patients were analysed, of which 395 and 90 respectively presented high persistent disease activity (from moderate to severe persistent), despite of conventional strategies implemented; therefore they underwent intervention by the MAT group between January and December of 2016. Clinical disease activity according to each disease (DAS28 and BASDAI measurements respectively) and adherence level (categories through the Morisky-Green test: no adherence, partial adherence, total adherence) were measured before and after the MAT intervention. The impact on disease activity and adherence level was determined through the McNemar test for independent samples Results: A significant increase in the proportion of patients in total adherence level was found for both diseases when comparing the initial and final measurements after the intervention by the MAT (table 1). Furthermore, statistical significant differences in the disease activity level were found, identifying a reduction in the proportion of patients with moderate to severe disease activity (Graph 1, A and B) after the MAT intervention Figure 1 A) Disease Activity in patients whit RA (DAS28); B) Disease Activity in patients whit SpA (BASDAI) Conclusions: The intervention by the MAT interprofessional group is an efficient strategy impacting the disease activity and therapeutic adherence of RA and SpA patients, improving their clinical outcomes and the natural history of the disease. These findings are relevant and may highlight the potential benefits for the implementation of this approach in patients with devastating autoimmune diseases. Disclosure of Interest: None declared